(untitled) (Bangladesh Journal of Plant Breeding and Genetics, 2016)
Genetic diversity of 45 traditional Bangladeshi boro rice genotypes was studied through Mahalanobis D2 statistics and was grouped into six clusters. The inter-cluster distances were higher than intra-cluster distances indicating wider genetic diversity among the genotypes of different clusters. The intra-cluster distances were lower in all the cases reflecting homogeneity of the genotypes within the cluster. The cluster V contained the highest number of genotypes (14) and the cluster I and VI contained the lowest (4) number. The highest intra-cluster distance was noticed for the cluster VI and the lowest for cluster V. The highest inter-cluster distance was observed between cluster I and VI followed by cluster II and VI, cluster I and V and the lowest between cluster II and IV. The genotypes from cluster VI could be selected as parents for hybridization for producing transgressive segregants. The highest cluster means for yield, grains per panicle and grain length-breath ratio were obtained from cluster I; whereas higher yield, grain breath, 1000 grain weight, flag leaf area, shortest growth duration were obtained from cluster V. Therefore, more emphasis should be given on cluster I, cluster V and cluster VI for selecting genotypes as parents to produce new recombinants with desired traits.